808-Nm Near-Infrared Laser Photobiomodulation versus Switched-Off Laser Placebo in Major Aphthae Management: A Randomized Double-Blind Controlled Trial - Claudio Pasquale; Esteban Colombo; Stefano Benedicenti; Antonio Signore; Andrea Amaroli (Applied Sciences, 2021)
Background: the aphtha is one of the most common oral mucosal ulcerations and presents as a painful punched-out sore. Systemic and topical medications are used to reduce inflammation and pain and to support the natural period of remission. Alternative treatment modalities have been requested to relieve pain and improve its healing. In this regard, photobiomodulation, which is a manipulation of cells’ metabolism through an energy transfer by light sources of non-ablative or thermal intensity, could support aphtha management. The predictor variable of our research was the photobiomodulation through higher energy and power irradiated through a handpiece with a flat-top beam profile. The primary end point was the complete healing of the aphtha, defined as the time from the irradiation to the complete recovery. The secondary end point was pain relief, evaluated daily through the visual analogue scale (VAS), from the irradiation to 24 and 48 h after. Methods: a randomized, double-blind, controlled trial was conducted according to the CONSORT guideline. Irradiation was performed through an 808-nm diode laser with flat-top handpiece, and 1 W, 1 W/cm2, 60 J, 60 J/cm2 for 60 s on a spot-size area of 1 cm2. Time of complete healing and pain evaluation by VAS scale were evaluated. Results: between 1 January, 2020 and 1 March, 2021, 126 patients were screened for the study at the Department of Surgical and Diagnostic Sciences, University of Genoa, Italy. Sixty patients were randomly assigned (30 in the photobiomodulation group and 30 in the placebo group). Patients of the photobiomodulation group experienced complete healing in an average time of 8.13 days ± 1.69 (min 5–max 10 days), while for the placebo group the average time extended to 30.76 ± 4.63 days (min 25–max 42 days). Patients of the photobiomodulation therapy group experienced a statistically significant reduction in pain and discomfort 24 and 48 h after treatment (p < 0.05); the reduction was statistically higher (p < 0.05) 48 h after treatment compared to 24 h after. Conclusions: photobiomodulation at the parameters and modality of irradiation proposed accelerates the healing recovery and reduces pain compared to the patients treated with the placebo.